The Effect of Using E-Leaflets via Whatspp as an Educational Medium on the Knowledge and Attitudes of Adolescent Girls Regarding Anemia - Annisa Ika Safitri; Atikah Adyas; Dewi Woro Astuti (Jurnal Kesehatan Cendikia Jenius, 2025)
Anemia remains a major health problem among adolescent girls in Indonesia, with a prevalence of 22.7%, and in Lampung Province reaching 57.6%. Poor dietary habits and low levels of knowledge and attitudes toward anemia are key contributing factors that require attention. This study aims to determine the effect of using e-leaflets via WhatsApp as an educational medium on the knowledge and attitudes of adolescent girls regarding anemia at the Surya Mandiri Orphanage. The study employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 60 adolescent girls were selected using a total sampling technique. Data were collected using a digital questionnaire distributed through Google Forms, while the intervention was delivered in the form of e-leaflet education via WhatsApp for seven days in June 2025. Data analysis using the Wilcoxon test showed a p-value of 0.001 (p<0.05) for both knowledge and attitude variables, indicating a significant effect of e-leaflet education on improving the knowledge and attitudes of adolescent girls regarding anemia. In conclusion, digital nutrition education using e-leaflets is effective in enhancing adolescent health literacy in anemia prevention. Therefore, it is recommended that e-leaflets distributed via WhatsApp be continuously used as an innovative nutrition education medium in adolescent and social institution settings.